FIBER TO THE DESK MENGGUNAKAN APLIKASI CISCO PACKET TRACER - Fikri Ardiansah; Fredy Kusuma Nugraha; M. Ashof Azria Azka (Jurnal Sains dan Teknologi, 2023)
The demand for higher bandwidth is increasing along with developments in communication technology. To solve this problem, many parties use optical cables as the backbone of communication network cabling, especially in large data centers. Projects such as FTTH (Fiber to the Home) and FTTB (Fiber to the Building) have also been undertaken to provide better service to customers. In recent years, to take advantage of the future benefits of optical cables, Fiber to the Desk (FTTD) has begun to be recommended specifically for enterprises, financial institutions, and federal agencies. This is because FTTD can provide high security and high data transmission speed. This article will provide a more detailed guide on implementing FTTD and its benefits and designing FTTD using the Cisco Packet Tracer application.